The sensitivity of electrodiagnostic criteria in subtype identification at the presentation in patients of Guillain-Barre syndrome - L.Mathukumalli, Neeharika; Yaranagula, Sai Deepak; A Kanikannan, Dr. Meena; Chepuru, Ramesh; Yareeda, Sireesha; Sarva, Sailaja; Borgohain, Rupam (International Journal of Medical Research and Review, 2020)
Introduction: Electrophysiology plays a pivotal role in identifying various GBS subtypes. Despite having many electrodiagnostic criteria,studies addressing their applicability in patients of GBS at diagnosis are quite a few. Purpose: This study evaluates the sensitivity of 5 known electrophysiological criteria in patients with GBS at the time of presentation. Material & Methods: Clinical and electrophysiological data of GBS patients admitted with us between January 2011 and December 2016 were collected retrospectively from our hospital database, compiled and analyzed. For each patient, 5 different criteria for the electrophysiological diagnosis of GBS were applied, and the sensitivity of these 5 criteria in the diagnosis was evaluated. Results: A total of 288 patients were included. Closer concordance was noted between the criteria in diagnosing axonal subtype (Range- 36.81% to 41.32%).Italian criteria had the highest sensitivity (41.32%). There was a wider variation in the diagnosis of AIDP (Range- 19.79 to 34.72%). Hadden criteria showed the highest sensitivity (34.72%) closely followed by Ho et al (34.02%). Conclusion: As the timing of Nerve Conduction Studies (NCS) and the severity of disease influence the grouping of each patient into a specific electrophysiologic subtype, one should be cautious in interpreting electrodiagnosticdata. Serial nerve conduction studies may be required to subtype each patient as electrophysiology evolves over the first few weeks of illness.